2022
DOI: 10.1111/ajco.13673
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of a smoking cessation checklist implemented within Australian cancer services

Abstract: Introduction:The detrimental impact of smoking tobacco can be mitigated when cancer patients quit smoking. Smoking cessation clinical pathways are inconsistently implemented within Australian cancer services. The aim of this study was to pilot test and evaluate the reach, adoption, and implementation of a smoking cessation checklist within oncology services. Methods:The checklist was implemented over a 6-month period in medical and radiation oncology services at two metropolitan and one rural hospital. The RE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Previous research in psychiatry settings reported the routine provision of brief smoking cessation advice at moderate levels and smoking status documentation as low as 50%, even after implementing system change interventions, intensive staff training and highly targeted smoking cessation interventions (Lappin et al, 2020;Metse et al, 2018;Prochaska et al, 2004;Williams et al, 2015;Wye et al, 2009Wye et al, , 2010Wye et al, , 2017Young et al, 2022). However, our study found high smoking status documentation (88%) prior to the system change intervention, likely related to new laws in 2015 that prohibited smoking at Queensland hospitals, which motivated improved smoking status documentation for inpatients and development of the Pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in psychiatry settings reported the routine provision of brief smoking cessation advice at moderate levels and smoking status documentation as low as 50%, even after implementing system change interventions, intensive staff training and highly targeted smoking cessation interventions (Lappin et al, 2020;Metse et al, 2018;Prochaska et al, 2004;Williams et al, 2015;Wye et al, 2009Wye et al, , 2010Wye et al, , 2017Young et al, 2022). However, our study found high smoking status documentation (88%) prior to the system change intervention, likely related to new laws in 2015 that prohibited smoking at Queensland hospitals, which motivated improved smoking status documentation for inpatients and development of the Pathway.…”
Section: Discussionmentioning
confidence: 99%
“…An app specifically designed for cancer patients showed higher 2-month quit rates compared with a widely available general smoking cessation app when tested in a pilot randomised controlled trial [ 30 ]. Focussed training for health care workers and the appointment of “clinical champions” improved the implementation of a smoking cessation checklist in three Australian hospital oncology services, two metropolitan and one rural [ 31 ]. Systematic implementation of smoking cessation in cancer centres has not had extensive study and the Care to Quit Study, a stepped wedge cluster randomized, controlled trial (RCT), will investigate this across multiple sites in Australia [ 32 ].…”
Section: Tobacco Treatment In Cancer Clinics and Hospital Settingsmentioning
confidence: 99%
“…Cost‐benefit, cost‐analysis, and cost‐minimization analysis provide researchers with frameworks to guide economic evaluations, however, numerous design decisions remain in order to make any analysis achievable and appropriate 4 . In addition, these evaluations often focus on specific interventions or trials, 5 or comparisons across treatments 6–8 and the impact on patients, but not the impact at an organizational level where many trials are undertaken.…”
Section: Introductionmentioning
confidence: 99%